Estabilidade oxidativa de hambúrguer de salmão enriquecido com fibra utilizando farinha de uva e aveia. - Cilli, Lilian Pinheiro De Lima [UNIFESP] (2018)
The agroindustrial residue of the grape byproduct is a discard of the industrialization of wines and grape juice with high antioxidant potential due to the presence of phenolic compounds and remaining anthocyanins in this residue. The objective of this work was to evaluate the effect of the addition of dehydrated grape pomace on the lipid oxidation of frozen salmon burger at – 18°C for 6 months. Two concentrations of FBU (1%), FBU (2%) and the chemical, physicochemical and sensorial characteristics of the products were compared with burgers without antioxidant (Control) and synthetic antioxidant (0,01% BHT). The pomace of the Isabel grape (peels and seeds) dehydrated by air convection at 40°C for 72 hours presented higher phenolic compound contents (669,88mg GAE/100g), anthocyanins (36,45mg cyaniding 3-glycoside/100g) and dietary fiber (31,79%) and the powder by spray dryer showed phenolic content in there conditions (ensaio 5) of (162,63mg GAE/100g), anthocyanins (16,58mg cyaniding 3-glycoside/100g). The ethanolic extracts of the dehydrated pomace showed high antioxidant activity evaluated by the DPPH (73,31%) and ABTS (236,81 μmol de Trolox/g) methods. In vitro cytotoxicity of grape flour was also evaluated using BALB/c 3T3 cells and the results showed that the aqueous extracts were non-toxic. The grape flour showed higher antioxidante potential than synthetic antioxidante BHT to delay lipid oxidation of salmon Burger during storage at -18°C for 6 months, and the antioxidante effect was dose-dependent. The hamburger with grape marc flour presented lower (P<0,05) formation of thiobarbituric acid reactive substances (TBARS), showing a protective effect superior to that observed with the synthetic antioxidant BHT. The addition of 1% of grape flour did not significantly alter the texture prolife of the samples that was similar to that of the Control and BHT treatments. The addition of grape flour significantly altered (P<0,05) the instrumental color of the hamburger samples (< L*, < C* e < h*). Despite the greater preference of consumers for the color and appearence of the burgers of Control and BHT treatments, all the samples of all the treatments presented high sensory acceptance índices (sensory notes > 6 for all atributes evaluated).